Subjetividade, família e violência: repercussões no adolescente contemporâneo. - Fonsêca, Célia Maria Souto Maior de Souza (2006)
It is in common authority that juvenile violence has reached alarming proportions in Brazil and in other parts of the world. In our country, it is evident that where the violence, in its most diverge forms of expression has been present, forming part, and at times, the model of identification in many of our adolescent, serving them as a standard form of conduct and self affirmation. We form part of a culture, which cohabits condescendingly in a scene, where children and young people walk about aimlessly in the streets of our cities. The acts of violence which follow, falI easily in the ruIe of vulgarity and commonplace, so gradually loosing the extraordinary character and brutality, which is inherent. This study is on juvenile violence. The focus was on the Brazilian Culture paying special attention to the contemporary Family, the role of the media was discussed, and, in the end, concluded that the effect of alI these diverge factors interacted with the subjectivity of juvenile violence. It is interesting that the violence, while the situation affects mankind, and treating this research qualitatively, in a phenomenal perspective, the dialogue was the starting point. This dialogue was from the collected evidence, such as the notes from the experience of representatives of the culture near to the juvenile violence. A judge from the Child and Juvenile Court, a journalist and members of two of the families, whose children were involved in acts of violence, either as a victim or attacker, were interviewed. The method of analysis was an understanding of the collected information from the evidence in contrast to the theoretic ideas in question. Aspects of the Brazilian Culture which facilitate the expression of violence were identified in the study; it brought to light a fragile and uncompromising family regarding the education of their children; a negligent and insensitive Society to the needs of the children; politicians indifferent to the poverty of the country; a superficial Media where the emphasis is in the hidden interest of the Market Economy, where Ethics and Morality do not dictate the ruIes of conduct and social act. We are face to face with contemporary man in his abandonment. In the end we recognize in violence alI the potential of chaos, not only in the manner of its destructiveness, bust also in the breeding potential, from which, however, we recognise it in its legal proceedings.